2023
DOI: 10.1038/s41598-023-27585-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduced bone formation and increased bone resorption drive bone loss in Eimeria infected broilers

Abstract: Coccidiosis is an economically significant disease in the global poultry industry, but little is known about the mechanisms of bone defects caused by coccidiosis; thus, the study focused on effects of coccidiosis on the bone homeostasis of young broiler chickens. A total of 480 male Cobb500 broilers were randomly allocated into four treatment groups, including an uninfected control consuming diet ad libitum, two infected groups were orally gavaged with two different concentrations of sporulated Eimeria oocysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 123 publications
1
37
0
Order By: Relevance
“…An imbalance in gut microbiota has been associated with bacterial translocation and chronic inflammation [21,48]. The inflammation often leads to an increased immune response and bone resorption in the bone marrow, consequently reducing bone formation, as observed in Eimeria-challenged or lipopolysaccharide-challenged broilers [49,50]. Significant bone loss has been noted in various models of intestinal inflammation, including dextran sulfate sodium-induced chemical injury, adoptive T cell transfer of colitis, and Salmonella enterica infection [51].…”
Section: Discussionmentioning
confidence: 99%
“…An imbalance in gut microbiota has been associated with bacterial translocation and chronic inflammation [21,48]. The inflammation often leads to an increased immune response and bone resorption in the bone marrow, consequently reducing bone formation, as observed in Eimeria-challenged or lipopolysaccharide-challenged broilers [49,50]. Significant bone loss has been noted in various models of intestinal inflammation, including dextran sulfate sodium-induced chemical injury, adoptive T cell transfer of colitis, and Salmonella enterica infection [51].…”
Section: Discussionmentioning
confidence: 99%
“…While the trabecular bone quality was not affected by the treatments in the NCP groups, it was improved in the LCP groups as Met levels increased. As previously mentioned, trabecular bone is more responsive to immune responses [ 47 , 48 , 49 ], and one previous study showed that the bone mineral loss during coccidiosis occurred more in the trabecular bone [ 7 ], so it is plausible to hypnotize that instead of being accumulated as Hcy, the extra Met supplementation exerted its functional roles, such as antioxidant capacity, immunomodulatory effects, and collagen synthesis [ 15 , 50 ], especially in the LCP groups where the supply of other essential and non-essential amino acids was also reduced. Consequently, trabecular bone quality may have improved, as evidenced by the increased trabecular number and connectivity density.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have highlighted its detrimental effects on nutrient utilization, intestinal integrity, and the growth performance of birds [ 2 , 3 , 4 , 5 ]. On the other hand, previous research has also documented a range of adverse outcomes on bone health by coccidia infection, including reduced bone mineralization leading to greater porosity in cortical bone, diminished bone mineral density, weakened bone strength, and increased trabecular bone resorption [ 6 , 7 ]. These findings underscore the systemic impact of coccidiosis, extending beyond the gastrointestinal tract to affect skeletal development and integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Th ), volume of total pores ( Po. V (tot) ), and total porosity percentage ( Po (tot) ) were analyzed and quantified ( Lee et al, 2023 ), as these bone traits are known to be correlated with the bone quality and bone growth status in poultry species ( Lee et al, 2023 ; Tompkins et al, 2023 ). Additionally, bone size, including whole bone length, diaphyseal width, and cortical bone thickness, were measured using the CTAn ruler tool.…”
Section: Methodsmentioning
confidence: 99%